Optically Switchable MeV Ion/Electron Accelerator - Itamar Cohen (Applied Sciences, 2021)
The versatility of laser accelerators in generating particle beams of various types is often promoted as a key applicative advantage. These multiple types of particles, however, are generated on vastly different irradiation setups, so that switching from one type to another involves substantial mechanical changes. In this letter, we report on a laser-based accelerator that generates beams of either multi-MeV electrons or ions from the same thin-foil irradiation setup. Switching from generation of ions to electrons is achieved by introducing an auxiliary laser pulse, which pre-explodes the foil tens of ns before irradiation by the main pulse. We present an experimental characterization of the emitted beams in terms of energy, charge, divergence, and repeatability, and conclude with several examples of prospective applications for industry and research.